INTEGRASI SISTEM KEAMANAN RUMAH PINTAR BERBASIS ESP32-CAM DAN SENSOR PIR DENGAN NOTIFIKASI REAL-TIME MELALUI WHATSAPP BOT - Hayadi Hamuda; Anjar Setiawan (SKANIKA: Sistem Komputer dan Teknik Informatika, 2025)
A smart home is a system that basically consists of intelligent elements that are interconnected and integrated with each other through the use of internet networks based on the Internet of Things. Today, smart home technology has been utilised in various rooms in contemporary homes. Several components, such as the ESP32-Cam microcontroller, of these smart home devices are installed in the room and include a motion sensor or PIR (Passive Infrared Receiver), buzzer, and WhatsApp notification software. When motion or activity is detected in the room, the components connected and integrated with the internet network will send notifications to a laptop or WhatsApp messaging programme in the form of text and photos. The results of tool testing and overall system testing data show that the PIR sensor can detect motion at a distance of 1 to 3 metres marked by the activation of the buzzer and the appearance of WhatsApp messages with an average delay of 1 to 3 seconds. Experiments were also carried out based on the length of the 5-pin USB cable, and the results showed that the length of the cable affected the delay in sending WhatsApp notifications in addition to wifi or internet connection. WhatsApp notifications take longer to send the longer the cable is. By using this smart home appliance, home dependability and security can be improved.